Konsep Zakat Mal dalam Islam dan Persepuluhan dalam Agama Kristen - Khairunnisa, Roza; Arifinsyah, Arifinsyah; Siregar, HusnaSari (TSAQOFAH, 2024)
Every religion certainly has a way of improving the welfare of all its followers, by sharing with fellow living creatures, helping each other, as a form of compassion for one's brothers. One form of effort by the people to strengthen brotherhood is zakat in the context of the Islamic religion and in the Christian religion it is known as tithe. This research aims to deepen knowledge of the concept of zakat mal in Islam and tithing in Christianity, to find out the essence of implementing the concept of zakat mal and tithing, and to look for comparisons between the two. This research uses a type of library research (Library Research). This research uses anthropological methods. This research uses a descriptive approach. The researcher uses data analysis techniques in the form of content analysis (content analysis) of library research where the data sources are books and documents and literature in a form that is others, providing input and transformative thoughts about the concept of zakat mal and tithing so as to provide clearer information. Based on the findings from this research, the concept of zakat mal and tithing is different even in terms of the meaning of giving wealth to other people by hoping for blessings from God. However, in the concept of zakat mal, someone who wants to give zakat mal must have excess assets and meet the requirements of the nishab and haul, while tithing does not have a requirement to carry out the teachings of tithing, anyone can give tithe as long as they have assets and it is not forced if there is none then it is permissible not to give tithe. The implementation of mall zakat is of course based on the provisions set by Allah, in harmony, the conditions have been explained in the Al-Qur'an, then you can give your zakat to the mall zakat manager to distribute it to people who are entitled to receive it. Likewise, tithe can be given one tenth of the assets owned to the church management.